2021
DOI: 10.29309/tpmj/2021.28.06.4778
|View full text |Cite
|
Sign up to set email alerts
|

Shaft of humerus fracture managed by anteromedial plating through anterolateral approach.

Abstract: Objective: To assess the use of anteromedial plating in the shaft of humerus fractures concerning the union of fracture and to assess the frequency of complications associated with this approach. Study Design: Cross Sectional study. Setting: United Medical and Dental College, Shaheed Muhatarma Benazir Bhutto Medical College Lyari and Khairpur Medical College. Period: 15 January 2016 to 15 January 2019. Material & Methods: All the patients aged 18 years or over presenting with the shaft of humerus fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The excellent functional outcome was achieved in 165 (73.3%) cases and good functional outcome in 58 (25.8%) cases. A fair outcome was achieved in two (0.9%) of the cases [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The excellent functional outcome was achieved in 165 (73.3%) cases and good functional outcome in 58 (25.8%) cases. A fair outcome was achieved in two (0.9%) of the cases [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lateral plating was performed between January 2018 and December 2021, and then all patients received anteromedial plating (Fig. 2) since the evidence showed that AM plating has signi cant advantages over lateral plating [18,19]. None of the fractures was shortened.…”
Section: Surgical Methodsmentioning
confidence: 99%